Propagation of Cannabis for Clinical Research: An Approach Towards a Modern Herbal Medicinal Products Development - Chandra, Suman; Lata, Hemant; ElSohly, Mahmoud A. (Frontiers in Plant Science, 2020)
Cannabis (Cannabaceae) is one of the oldest cultivated plants for fiber, food and medicine. The plant has been reported to contain over 560 different compounds belonging to a diverse group of chemical classes, the most important of which is the cannabinoids. There are 120 cannabinoids reported so far. Among the cannabinoids, D9-tetrahydrocannabinol (D9-THC) and cannabidiol (CBD) are the two major compounds with very different pharmacological profile and a tremendous therapeutic potential. Due to its medicinal properties, cannabis has gained a lot of popularity in the last few decades. However, there are many challenges in bringing cannabis from grow-farms to pharmaceuticals. Among many, one important challenge is to maintain the supply chain of biomass, which is consistent in its cannabinoids profile. Cannabis is a wind-pollinated species which is highly allogamous (cross fertilization) in nature. If grown from seeds, it is very difficult to maintain the consistency in cannabinoid profile of produced biomass. A high degree of plant to plant variation in the cannabinoid profile is also observed. The problem becomes worse when more than one variety are grown together. To avoid this process, male plants are removed from growing fields as they appear. Even with that practice, still there are fair chances of cross fertilization. Therefore, controlled indoor cultivation for screening, selection of high yielding female plants based on their cannabinoids profile and their conservation and multiplication using vegetative propagation and/or micropropagation is a suitable path to ensure consistency in biomass material. In this chapter, the botany and propagation of elite cannabis varieties will be discussed.